2014
DOI: 10.1016/j.jadohealth.2014.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Vulnerable Urban Youth in Five Global Cities

Abstract: Background Social capital is essential for the successful development of young people. The current study examines direct measures of social capital in young people in five urban global contexts. Methods The Well Being of Adolescents in Vulnerable Environments (WAVE) is a global study of young people aged 15 to 19 years living in disadvantaged, urban settings. Respondent Driven Sampling (RDS) was used to recruit approximately 500 participants from each site. The sample included 2339 young people (mean age 16.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Due to the stability of individual status characteristics of an individual, as a result of the effect of the integrating and socializing functions, we can assess the social norm of an individual, his social health, and social well-being (Marshall et al, 2014).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Due to the stability of individual status characteristics of an individual, as a result of the effect of the integrating and socializing functions, we can assess the social norm of an individual, his social health, and social well-being (Marshall et al, 2014).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Research in Johannesburg, South Africa found that being raised outside a two-parent family has a widespread, negative association with social capital for young people aged 15-19 years, as was the case for their peers in similarly disadvantaged, urban settings in Nigeria, China, India and the USA (Marshall et al, 2014).…”
Section: How Does Family Structure Affect Parenting and Adolescent Wementioning
confidence: 91%
“…Also, it is determined by the mass use of technology and technology within the urban space. More than that, the intensity of social contacts allows producing, discussing and implementing innovative artifacts [13]. But one of the consequences of social dynamics is the inevitability of conflicts between the old and the new generations.…”
Section: Methodsmentioning
confidence: 99%